2020
DOI: 10.1097/md.0000000000020420
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric and visualized analysis of global research on fungal keratitis from 1959 to 2019

Abstract: Background: Fungal keratitis is one of the leading causes of ocular morbidity. The prognosis of fungal keratitis is poorer than many other forms of keratitis but the research of which relatively lags behind. We conducted a bibliometric and visualized analysis in order to characterize the overall status, general trends and current foci of keratomycosis research field. Methods: Literature database ranged from 1959 to 2019 was obtained from web of science … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…In fact, different databases can be analyzed and mapped with visualization methods. [18][19][20][21][22][23][24][25] Heng Wong et al [24] in a bibliometric analysis study in which 100 groundbreaking articles in the field of eye were examined, it was reported that most of the publications were from the USA, as in our study. In this study, all types of articles were examined, 83% of the publications were original research articles and 15% of the publications were DR. [24] This shows that DR, which is the subject of our study, is one of the important issues in the field of eye diseases.…”
Section: 948supporting
confidence: 59%
“…In fact, different databases can be analyzed and mapped with visualization methods. [18][19][20][21][22][23][24][25] Heng Wong et al [24] in a bibliometric analysis study in which 100 groundbreaking articles in the field of eye were examined, it was reported that most of the publications were from the USA, as in our study. In this study, all types of articles were examined, 83% of the publications were original research articles and 15% of the publications were DR. [24] This shows that DR, which is the subject of our study, is one of the important issues in the field of eye diseases.…”
Section: 948supporting
confidence: 59%
“…This can thus play a role in governing policymaking [4]. Bibliometric analyses are used in various research fields, including ophthalmology [5][6][7]. Some reviews of the literature have been done in AI in ophthalmology [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…So, a study involving another disease, "fungal keratis" reveals that most of co-citation research is concentrated on the disease's epidemiology in and around keratomycosis. However, no evidence and correlation of mucormycosis can be established through this research (Cen et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 85%